Conference Review: the EAA 2017 in Maastricht (NL) - Roeland P Paardekooper (EXARC, 2017)
The annual conference of the European Association of Archaeologists (EAA) is an important venue for the presentation of any type of archaeology in Europe. This year, the conference was attended by about 1,800 archaeologists including about ten EXARC members. EXARC was involved in organising two sessions, one on live interpretation, and the other on experimental archaeology. We intend to be present again next year in Barcelona.